Analisis Kejadian Ibu Hamil dengan Preeklampsia di Puskesmas Tambora Jakarta Barat dan Puskesmas Padang Ratu Lampung Tengah - Sulistyaningsi, Eka; Nuraini, Hani; Tahun, Omega DR (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Preeclampsia is a condition that can be fatal in the condition of pregnant women who are in the field and require immediate medical attention. The mother may experience severe complications from preeclampsia, such as pulmonary edema, hemolysis, neurology, hepatic, coagulation and fibrinolysis, and blood viscosity. Prematurity, oligohydramnios, and intrauterine growth retardation (IUGR) are the result of fetal pre-eclampsia. Placidation failure is usually the initial cause of preeclampsia. This study aims to examine the prevalence of preeclampsia in the Padang Ratu Lampung Tengah Health Center and the Tambora Health Center in West Jakarta. This study uses a quantitative retrospective descriptive research design. 425 respondents formed the sample size used in this study, which was determined through Porpusif Random Sampling. Secondary data is the one used. To collect secondary data for the study, observation sheets were used, and patient files containing patients giving birth were examined. Since the data is on a categorical scale, the data analysis uses the Chi-Square test to detect connections between variables. Age, education, occupation, parity, and family income are the variables included in the analysis of this study about the incidence of preeclampsia pregnancy in Tambora Health Center in West Jakarta and Padang Ratu Health Center in Central Lampung. Each p-value (0.015, 0.011, 0.007, 0.011, 0.015) is less than 0.05. Age, education, occupation, parity, and family income were the characteristics analyzed in relation to the incidence of preeclampsia in pregnant women at Tambora Health Center and Padang Ratu Health Center in Central Lampung. It is important to assess age, education, employment, equality, and family income so that pre-eclampsia in pregnant women does not recur.  Keywords: Age, Employment, Parity, Preeklampsia   ABSTRAK Preeklampsia adalah kondisi yang mungkin bisa berakibat fatal dalam keadaan ibu hamil yang berada di lapangan dan membutuhkan perhatian medis segera. Ibu mungkin mengalami komplikasi parah dari preeklampsia, seperti edema paru, hemolisis, neurologi, hati, koagulasi dan fibrionlysis, dan viskositas darah. Prematuritas, oligohidramnion, dan retardasi pertumbuhan intrauterin (IUGR) adalah hasil dari pre-eklampsia janin. Kegagalan plasnasi biasanya merupakan penyebab awal preeklampsia. Penelitian ini bertujuan untuk mengkaji prevalensi kehamilan preeklamptik di Puskesmas Padang Ratu Lampun Tengah dan Puskesmas Tambora di Jakarta Barat. Penelitian ini menggunakan desain penelitian deskriptif retrospektif kuantitatif. 425 responden membentuk ukuran sampel yang digunakan dalam penelitian ini, yang ditentukan melalui Porpusif Random Sampling. Data sekunder adalah yang digunakan. Untuk mengumpulkan data sekunder untuk penelitian ini, lembar observasi digunakan, dan file pasien yang berisi pasien yang melahirkan diperiksa. Karena data berada pada skala kategoris, analisis data menggunakan uji Chi-Square untuk mendeteksi koneksi antar variabel. Usia, pendidikan, pekerjaan, paritas, dan pendapatan keluarga adalah variabel yang masuk dalam analisis penelitian ini tentang kejadian kehamilan preeklampsa di Puskesmas Tambora Jakarta Barat dan Puskesmas Padang Ratu di Lampung Tengah. Setiap p-value (0,015, 0,011, 0,007, 0,011, 0,015) kurang dari 0,05. Usia, pendidikan, pekerjaan, paritas, dan pendapatan keluarga adalah karakteristik yang dianalisis dalam kaitannya dengan kejadian preekalmsia pada ibu hamil di Puskesmas Tambora dan Puskesmas Padang Ratu LampungTengah. Penting untuk menilai usia, pendidikan, pekerjaan, kesetaraan, dan pendapatan keluarga agar pre-eklampsia pada wanita hamil tidak terulang kembali. Kata Kunci: Usia, Pekerjaan, Paritas, Preekalmsia